Distribution of phytochelatins, metal-binding compounds, in plant foods: A survey of commonly consumed fruits, vegetables, grains and legumes. (1st March 2021) - Dennis, Kristine K.; Liu, Ken H.; Uppal, Karan; Go, Young-Mi; Jones, Dean P.
Highlights: Metal-binding compounds, phytochelatins (PyCs), were characterized in plant foods. PyCs may impact metal bioavailability but quantities in the human diet are unknown. Five PyC types were detected across 20 commonly consumed plant foods. PyC2 -Glycine was at the highest concentrations and found in 18 of 20 foods. PyC3 -Glycine, PyC4 -Glycine, PyC2 -Alanine, and PyC2 -Glutamate were also found. Abstract: Phytochelatins (PyCs) are metal-binding compounds produced by plants. PyCs may reduce bioavailability of dietary toxic metals such as cadmium. However, the PyC concentrations in foods are unknown. The objective of this study was to analyze PyC contents in a subset of commonly consumed plant foods. Foods (20) across five groups were analyzed and PyCs quantified using liquid chromatography-mass spectrometry (LC-MS/MS). The impact of factors such as food processing were also explored. PyCs were in all 20 foods. Five PyC types were detected with PyC2 -Gly, PyC3 -Gly and PyC2 -Ala at quantifiable concentrations. PyC2 -Gly was found at the highest concentrations and most widely distributed. PyC2 -Gly concentrations were highest in fruits and root vegetables. Foods with increased processing tended to have reduced PyC concentrations. This survey of commonly consumed plant foods in the United States demonstrates PyCs are widely distributed and provides a foundation for understanding their concentrations and impact in the human diet.